ANALISIS PEMANFAATAN BANK SAMPAH UNTUK PENINGKATAN PENDAPATAN BAGI NASABAH BANK SAMPAH DALANG COLLECTION DI KOTA PEKANBARU - ,Eriyati, Desi Azzahra ,Hendro Ekwarso (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to find out how the use of the Garbage Bank to Increase Customer Income of the Dalang Collection Garbage Bank in Pekanbaru City. The research method is carried out by first collecting existing data and then clarifying, analyzing, then interpreting it so that it can provide solutions to problems. Based on the descriptive analysis of how the use of the Garbage Bank to Increase Customer Income of the Dalang Collection Garbage Bank in Pekanbaru City shows that all respondents (100%) before joining the Dalang Collection had no income but after joining the average income was 88.63% (39 people) of respondents who get income from making products as much as IDR 10,000-IDR 300,000 / month. The research also found that there were 9% (4 people) of respondents who earned income from making products as much as Rp.410,000-Rp.655,000/month. There are also 2.27% (1 person) of respondents who earn from making products as much as Rp.310,000-Rp.400,000/month. And income of Rp. 11.855.000  with an average total income of Rp. . 269.432    in a 1 month period. Keywords: Employment, Waste Savings, Customer Income.